2022
DOI: 10.1016/j.mtbio.2021.100181
|View full text |Cite
|
Sign up to set email alerts
|

Novel glucose-responsive nanoparticles based on p-hydroxyphenethyl anisate and 3-acrylamidophenylboronic acid reduce blood glucose and ameliorate diabetic nephropathy

Abstract: An insulin delivery system that self-regulates blood sugar levels, mimicking the human pancreas, can improve hyperglycaemia. At present, a glucose-responsive insulin delivery system combining AAPBA with long-acting slow release biomaterials has been developed. However, the safety of sustained-release materials and the challenges of preventing diabetic complications remain. In this study, we developed a novel polymer slow release material using a plant extract—p-hydroxyphenylethyl anisate (HPA). After block cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…(Thaipitakwong et al, 2018) The results of serum biochemical analysis demonstrated a significant decrease in serum glucose levels after administering metformin and metformin nanoparticles drug for 28 days to diabetic rats. This finding was consistent with several authors' previous results (Qiong Ma, et al,2022). Higher ALT levels are a risk factor for type 2 diabetes, indicating a possible role for increased hepatic gluconeogenesis and inflammation in the pathogenesis of type 2 diabetes.…”
Section: Disuccusionsupporting
confidence: 93%
“…(Thaipitakwong et al, 2018) The results of serum biochemical analysis demonstrated a significant decrease in serum glucose levels after administering metformin and metformin nanoparticles drug for 28 days to diabetic rats. This finding was consistent with several authors' previous results (Qiong Ma, et al,2022). Higher ALT levels are a risk factor for type 2 diabetes, indicating a possible role for increased hepatic gluconeogenesis and inflammation in the pathogenesis of type 2 diabetes.…”
Section: Disuccusionsupporting
confidence: 93%
“…Therefore, when the water absorbing ability of P(AAm-AAc-3-AAPBA) is larger than that of the PAAm layer, the bilayer hydrogel structure bends reversely [ 15 , 16 , 17 ]. The volume change in the PAAm hydrogel layer is positively correlated with that of the P(AAm-AAc-3-AAPBA) layer, but the variation is much smaller than that of P(AAm-AAc-3-AAPBA) [ 18 ]. Simultaneously, the hydrogels of AAc and AAm have good water absorption ability and softness, so the bi-directional bending angle can surpass 360°.…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al 123 employed a novel plant-derived p -hydroxyphenylethyl anisate and 3-acrylamidophenylboronic acid to form a shell to load insulin for diabetic treatment. The insulin core was self-assembly-encapsulated in the shell.…”
Section: Self-assembly Methodsmentioning
confidence: 99%